Inluence Of Religiosity Towards The Saving Interest At Islamic Banking With The Knowledge Of The People As Moderator Variable (Case Study On The People Of South Tanggerang City) - Astuty, Pudji; Umiyati, Umiyati (IKONOMIKA, 2018)
ABSTRACTThe purpose of this study is to analyze the influence of religiosity on the saving interest at Islamic Banking with the knowledge of the people as the moderator variable. This study was held at Tanggerang Selatan. The methods that is used to gather samples for this study is non-probability sampling and with the technique convenience sampling. The respondents in this study are the people of South Tanggerang City who saves their money at Islamic Banking, there are 100 respondents in total. The data gathered through questionnaire as the methods of survey. The data that are gathered then processed using multiple linear regression with interaction test (moderated regression analysis). The result of this study shows that there is significant influence between religiosity and the saving interest at Islamic Banking. the knowledge of the people and the saving interest at Islamic Banking also shows significant influence. The interaction between religiosity and knowledge as the moderator variable giving significant influence on the saving interest at Islamic Banking at the rate of significance bellow 0.05 or 5%. Keywords : Religiosity, The People’s Knowledge, saving interest at        Islamic Banking